Identification of CD4+ T-cell-derived CD161+ CD39+ and CD39+CD73+ microparticles as new biomarkers for rheumatoid arthritis. (February 2017) - Fan, Wenqiang; Wang, Wenxiang; Wu, Jie; Ma, Ling; Guo, Jinyan
Aim: This study aimed to identify CD4 + T-cell-derived microparticles (MPs) and investigate their roles in rheumatoid arthritis (RA).Methods: Synovial fluids from 34 RA, 33 osteoarthritis patients and 42 healthy individuals were analyzed by flow cytometry. Human fibroblast-like synoviocytes and peripheral blood mononuclear cells were cultured with or without isolated MPs, chemokines and cytokines were measured by ELISA.Results: CD4 + CD161 + CD39 + and CD4 + CD39 + CD73 + MPs were abundantly present in RA patients, which were positively or negatively correlated with RA features, respectively. Chemokines CCL20, CCL17 and CCL22, and cytokines IL-17 and IL-10 were influenced by these MPs in human fibroblast-like synoviocytes (HFLS) or PMBCs.Conclusion: CD4 + T-cell-derived CD161 + CD39 + and CD39 + CD73 + MPs could serve as new reciprocal biomarkers for RA evaluation.